Working Less to Take Care of Parents? Labor Market Effects of Family Long-Term Care in Four Latin American Countries - Marco Stampini; María Laura Oliveri; Pablo Ibarrarán; Diana Londo\~no; Ho June (Sean) Rhee; Gillinda M. James (Institute of Labor Economics (IZA), 2020)
We use data from time-use surveys and the Mexican Health and Aging Study (MHAS) to analyze the relationship between family long-term care (LTC) and female labor supply in four Latin American countries. Time-use survey data from Chile, Colombia, Costa Rica and Mexico shows that: (i) women provide the vast majority of family LTC; (ii) consistently across countries, women who provide LTC are less likely to work, and those who do work less hours per week and have a double burden of work and LTC. Multivariate analysis of longitudinal MHAS data shows that, after accounting for both individual and time fixed effects, parents' need for LTC is associated with both a significant drop in the likelihood of working (by 2.42 percentage points) and a reduction in the number of hours worked among women ages 50–64 who remain employed (by 7.03%). This finding has important gender equality implications. Also, in a region that is aging faster than any other in the world, social trends make this family provision of LTC unsustainable, increasing the need for policy action.
Keywords: J14; J16; J18; J21; J22; 330; female labor supply; Long-Term Care (LTC); elderly care; care dependence; time-use surveys; Mexican Health and Aging Study (MHAS); Latin America; Chile; Colombia; Costa Rica; Mexico